Effect of diesel particulate filter regeneration on fuel consumption and emissions performance under real-driving conditions. (15th July 2022) - Huang, Yuhan; Ng, Elvin C.Y.; Surawski, Nic C.; Zhou, John L.; Wang, Xiaochen; Gao, Jianbing; Lin, Wenting; Brown, Richard J.
Graphical abstract: Highlights: DPF regeneration performance was investigated under real driving conditions. Fuel consumption was increased by 13% for a 19-km trip with DPF regeneration. CO and THC emission factors were increased moderately during DPF regeneration. Total NOx was unaffected but NO2 /NOx ratio was greatly reduced by DPF regeneration. PM emission factor sharply increased by 27 times for a 19-km trip with DPF regeneration. Abstract: Diesel particulate filters (DPF) are widely adopted in diesel vehicles to meet the increasingly stringent emission regulations, which require continuous passive regenerations or/and periodic active regenerations to burn off the accumulated particulate matter (PM). In spite of many laboratory studies using DPF benches and engine/chassis dynamometers, there is currently a lack of investigation on DPF regeneration under real-world conditions. Therefore, this study was conducted to investigate the impact of active DPF regenerations on the fuel consumption and gaseous and particulate emissions performance of a diesel light goods vehicle under real-driving conditions by using the state-of-the-art portable emission measurement system. In total, 60 real-driving emission (RDE) tests (∼1200 km in total) were performed on the same route during the same periods of a day, to minimise the effect of uncontrollable real-world factors on the performance evaluation. The results showed that real-world active DPF regenerations occurred every 130 km for the studied vehicle. Although they did not occur frequently, DPF regenerations increased the trip-averaged fuel consumption rate by 13% on average. CO and THC emission factors tended to increase with DPF regenerations because the post combustion used to achieve the high exhaust temperature for regeneration of the filter occurred under oxygen-lean conditions. Total NOx emissions were not affected but NO2 /NOx ratio was greatly reduced by DPF regeneration due to lower NO oxidation by the diesel oxidation catalyst and higher NO2 reduction by the DPF. Finally, DPF regenerations sharply increased PM emission factors by 27 times compared with a trip without DPF regeneration, resulting in significant exceedance of the emission limit.